Escala de Respostas Ruminativas para Adolescentes - Pinto-Gouveia, José (2012)
The RRS is a 10-item scale that measures the individuals' tendency to ruminate when in a sad or depressed mood. This scale comprises two subscales: brooding (5 items) and reflection (5 items). To the statement "what you generally do, not what you think you should do when feel down, sad or depressed" respondents rated each item on a 4 point scale (1 = "almost never" to 4 = "almost always"). Thus, scores may range between 10 and 40, with higher scores indicating higher levels of ruminative responses styles.